Thai EFL Students’ Engagement in Field Teaching Practice in Indonesia Classroom Context - Hayemadeng, Miss Affaf (IAIN KENDARI, 2023)
The purpose of this qualitative study is to investigate the engagement of Thai EFL pre-service teachers during their field teaching practice in Indonesian classroom context at some schools in Kendari, South East Sulawesi, Indonesia. The data in this study is drawn from four Thai students who have completed their teaching practice the previous semester. The four participants were assigned to four schools, respectively. This study used reflective journals and in-depth interviews as the instrument to collect the data. The gathered data was analyzed using thematic analysis (V Braun, V Clarke, 2012). The findings showed that several aspects of the engagement of Thai EFL students while facing in their field teaching practice in Indonesian classroom context. First, they taught with enthusiasm and passion while teaching English in an Indonesian classroom. Second, they have a positive attitude with their students that can shape their learning experience. Third, they treat students with respect to become more effective when they can earn a class's respect. Last, stay motivated is their involvement during their field teaching practice. However, this study implies that they were engaged in field teaching practice in Indonesian classroom context